Neurobiological Study of Fish Brains Gives Insights into the Nature of Gonadotropin-Releasing Hormone 1–3 Neurons - Karigo, Tomomi; Oka, Yoshitaka (Frontiers in Endocrinology, 2013)
Accumulating evidence suggests that up to three different molecular species of GnRH peptides encoded by different paralogs of gnrh genes are expressed by anatomically distinct groups of GnRH neurons in the brain of one vertebrate species. They are called gnrh1, gnrh2, and gnrh3. Recent evidence from molecular, anatomical, and physiological experiments strongly suggests that each GnRH system functions differently. Here, we review recent advancement in the functional studies of the three different GnRH neuron systems, mainly focusing on the electrophysiological analysis of the GnRH-green fluorescent protein (GFP) transgenic animals. The introduction of GFP transgenic animals for the electrophysiological analysis of GnRH neurons greatly advanced our knowledge on their anatomy and electrophysiology, especially of gnrh1 neurons, which has long defied detailed electrophysiological analysis of single neurons because of their small size and scattered distribution. Based on the results of recent studies, we propose that different electrophysiological properties, especially the spontaneous patterns of electrical activities and their time-dependent changes, and the axonal projections characterize the different functions of GnRH1-3 neurons; GnRH1 neurons act as hypophysiotropic neuroendocrine regulators, and GnRH2 and GnRH3 neurons act as neuromodulators in wide areas of the brain.